Health effects of exposure to radon: implications of the radon bed mattress incident in Korea - Songwon Seo; Wi-Ho Ha; Jin-Kyu Kang; Dalnim Lee; Soojin Park; Tae-Eun Kwon; Young Woo Jin (Epidemiology and Health, 2019)
Radon is a naturally occurring radioactive material formed by the slow decay of uranium and thorium found in the earth’s crust or construction materials. Internal exposure to radon accounts for about half of the natural background radiation dose to which humans are exposed annually. Radon is a carcinogen and is the second leading cause of lung cancer following smoking. An association between radon and lung cancer has been consistently reported in epidemiological studies on mine workers and the general population with indoor radon exposure. However, associations have not been clearly established between radon and other diseases, such as leukemia and thyroid cancer. Radiation doses are assessed by applying specific dose conversion coefficients according to the source (e.g., radon or thoron) and form of exposure (e.g., internal or external). However, regardless of the source or form of exposure, the effects of a given estimated dose on human health are identical, assuming that individuals have the same sensitivity to radiation. Recently, radiation exceeding the annual dose limit of the general population (1 mSv/yr) was detected in bed mattresses produced by D company due to the use of a monazite-based anion powder containing uranium and thorium. This has sparked concerns about the health hazards for mattress users caused by radiation exposure. In light of this event, this study presents scientific information about the assessment of radon and thoron exposure and its human implications for human health, which have emerged as a recent topic of interest and debate in society.